ANALISIS EFISIENSI USAHATANI JAGUNG ANGGOTA DAN NON-ANGGOTA KELOMPOK TANI DI KECAMATAN MARGA TIGA KABUPATEN LAMPUNG TIMUR - Ni Nyoman Tri Santiasih; Dyah Aring Hepiana Lestari; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to analyze the level of technical efficiency, technical inefficiency factors, and economic efficiency of corn farming of members and nonmembers of farmer groups. This research was conducted in the Gedung Wani and Negeri Katon Villages of Marga Tiga District, East Lampung. Respondent farmers were determined intentionally with a simple random sampling. This research use a survey method and the data were collected in February-March 2019. Technical efficiency, technical inefficiency factors, and economic efficiency were analyzed using the Stochastic Frontier 4.1.  The results showed that corn farming in Marga Tiga District was technically efficient, with an efficiency of 0.95. The number of family members can increase technical inefficiency, age and experience can reduce technical inefficiency, while education and farmer groups membership do not affect technical inefficiency.  Corn farming in Marga Tiga District was also economically efficient with an efficiency level 0.89 for members of farmer groups and 0.90 for non-members of farmer groups.Key words: corn farming, efficiency, farmer groups